Comparative Outcomes of Standard Perioperative Eye Drops, Intravitreal Triamcinolone Acetonide-Moxifloxacin, and Intracameral Dexamethasone-Moxifloxacin-Ketorolac in Cataract Surgery - Robin K. Kuriakose; Soungmin Cho; Saman Nassiri; Frank S. Hwang (Journal of Ophthalmology)
Background. Since the advent of cataract surgery, topical eye drops have been the mainstay of postoperative prophylaxis and treatment. Due to factors such as high expenses and poor patient compliance, there has been a growing interest and acceptance of “dropless” or “less drops” alternatives. The purpose of this study is to compare the effectiveness of intravitreal triamcinolone acetonide-moxifloxacin and intracameral dexamethasone-moxifloxacin-ketorolac to a standard eye drop regimen in controlling postoperative inflammation, corneal edema, and intraocular pressure (IOP) among cataract patients. Methods. A retrospective longitudinal comparative study among 619 consecutive eyes receiving either a standard eye drop regimen, intraoperative triamcinolone acetonide-moxifloxacin, or dexamethasone-moxifloxacin-ketorolac was performed between October 2016 and December 2020. Primary endpoints at postoperative day one (POD1), week one (POW1), and month one (POM1) included corneal edema, anterior chamber inflammation (ACI), and IOP. Results. Throughout the postoperative time points, there were no significant differences in corneal edema between intravitreal triamcinolone acetonide-moxifloxacin versus the standard eye drop therapy (OR [95% CI]: 1.09 [0.82, 1.45], P=0.54) and intracameral dexamethasone-moxifloxacin-ketorolac versus the standard eye drop treatment (OR [95% CI]: 1.22 [0.89, 1.67], P=0.22). The postoperative ACI severity was lower in the dexamethasone-moxifloxacin-ketorolac group than in the triamcinolone acetonide-moxifloxacin group by 35% on postoperative day 1 (P=0.01). The differences at subsequent postoperative time points were not statistically significant (P=0.27 and P=1.00 for POW1 and POM1, respectively). IOP at POM1 follow-up visit was statistically significantly higher for the triamcinolone acetonide-moxifloxacin group (mean (±SD): 15.64 (4.26)) than the dexamethasone-moxifloxacin-ketorolac (mean (±SD): 14.16 (4.02)) (P<0.01). There was no statistical difference in rates of CME (P=0.16), and there were no cases of endophthalmitis. Conclusions. Intravitreal triamcinolone acetonide-moxifloxacin and intracameral dexamethasone-moxifloxacin-ketorolac demonstrate similar levels of efficacy to a standard eye drop regimen after cataract surgery. This study reinforces them as viable alternatives to traditional postoperative drops.